2002
DOI: 10.1007/bf03256188
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine-Provoked Hepatotoxicity and Possible Aetiopathological Role of Glutathione in the Events

Abstract: The antiepileptic drug (AED) carbamazepine is widely used in the treatment of different kinds of seizures as well as affective and behavioural disorders. This paper presents an epidemiological study of carbamazepine-induced hepatic injuries and death, and describes the possible mechanisms of its toxicity. A retrospective analysis of clinical data revealed that the likelihood of hepatic death was comparatively higher in children, particularly when they were receiving medication with multiple AEDs, whereas rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 84 publications
0
39
1
1
Order By: Relevance
“…We established cytoprotectiv estrategies concerning the hepatotoxicity associated with carbamazepine therapy. The toxicity was investigated in hepatocytes induced by phenobarbital (CYP450 inducer), because of the probability that the intermediate areneoxides formed in biotransformation might be the causes of the toxicity (Bavdekar et al;Kalapos, 2002;Madden et al, 1996;Shear & Spielberg, 1988). The results of our study showed that oxidative stress was involved in hepatotoxicity induced by carbamazepine and its metabolites.…”
Section: Discussionmentioning
confidence: 74%
“…We established cytoprotectiv estrategies concerning the hepatotoxicity associated with carbamazepine therapy. The toxicity was investigated in hepatocytes induced by phenobarbital (CYP450 inducer), because of the probability that the intermediate areneoxides formed in biotransformation might be the causes of the toxicity (Bavdekar et al;Kalapos, 2002;Madden et al, 1996;Shear & Spielberg, 1988). The results of our study showed that oxidative stress was involved in hepatotoxicity induced by carbamazepine and its metabolites.…”
Section: Discussionmentioning
confidence: 74%
“…The first pathway includes the formation of carbamazepine-10, 11-epoxide (CBZ-EP), the principal metabolite of CBZ with anticonvulsant properties, which is almost completely hydrolyzed to 10,11-dihydro-10,11-trans-dihydroxycarbamazepine (diOH-CBZ) before excretion. This pathway is mainly mediated by the cytochrome P450 (CYP) CYP3A4 isozyme, while a minor role is attributed to CYP2C8 (Kalapos, 2002). Another pathway is the hydroxylation of the six-membered aromatic ring, leading to the formation of 2-hydroxycarbamazepine (2-OH-CBZ), 3-OH-CBZ, 1-OH-CBZ, etc.…”
Section: Carbamazepine Tissue Distributionmentioning
confidence: 98%
“…The clinical use of CBZ, an anticonvulsant, has been associated with a variety of idiosyncratic adverse reactions, such as generalized reactions, hepatotoxicity, and hematological disorders (Hart and Easton, 1982;Shear et al, 1988;Kalapos, 2002). CBZ-induced adverse reactions have been reported in as many as 30 to 50% of all patients treated with this drug (Pellock, 1987;Durelli et al, 1989).…”
mentioning
confidence: 99%
“…Although the mechanisms behind these adverse reactions are not clear, they are proposed to result from the formation of chemically reactive metabolites (Shear et al, 1988). An arene oxide intermediate has been postulated to be responsible for the idiosyncratic toxicity of CBZ (Pirmohamed et al, 1992;Lillibridge et al, 1996;Madden et al, 1996;Amore et al, 1997;Masubuchi et al, 2001;Kalapos, 2002). However, it has been difficult to achieve definitive proof of the arene oxide due to its high instability.…”
mentioning
confidence: 99%